2023
DOI: 10.1017/brimp.2023.3
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of adults with stroke attending a peer-led peer-support group

Abstract: Purpose: Peer-support groups for stroke survivors are often organized and facilitated by health authorities and disability related organizations within rehabilitation programs. However, the benefits of peer-led, peer-support groups have not yet been evaluated. The purpose of this study was to explore participants’ experiences in a community-based, peer-led, peer-support group for stroke survivors. Materials and Methods: Semi-structured interviews were conducted and analyzed following con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Meanwhile, peer support is crucial. Studies have indicated that peer support may contribute to the prognosis of stroke by facilitating connections between stroke survivors and like-minded individuals in the community [ 62 , 63 ]. Peer support also plays a positive role in hypertension control [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, peer support is crucial. Studies have indicated that peer support may contribute to the prognosis of stroke by facilitating connections between stroke survivors and like-minded individuals in the community [ 62 , 63 ]. Peer support also plays a positive role in hypertension control [ 64 ].…”
Section: Discussionmentioning
confidence: 99%